Distance and choice of field: Evidence from a Norwegian college expansion reform - Tora K. Knutsen; Jørgen Heibø Modalsli; Marte Rønning (Statistics Norway, Research Department, 2020)
How can geographical proximity to college explain field of study choices? We empirically address this question using the major expansion of university colleges in Norway in the second half of the twentieth century, when 33 new education institutions were established in areas that did not previously have any institutions for higher education. Our findings indicate that take-up of the relevant educations (nursing, engineering and business administration) increased substantially with the establishment of new colleges. However, we do not find evidence of an increase in education on earnings capacity overall, suggesting that the new colleges shifted individuals on the intensive rather than extensive margin, between education tracks of similar length. We discuss challenges related to the estimation of education choices in a population that often started higher education late, well into their twenties, and also document substantial gender differences in the take-up of different higher education opportunities.
Keywords: D31; I23; J62; 330; University access; Gender differences; Field of study; Geospatial variation